Interaction of floor space, dietary energy level and feed enzyme influencing growth performance of growing turkey - KUMAR, DEV; ROKADE, J J; MAJUMDAR, S; BHANJA, S K; MANDAL, A B (The Indian Journal of Animal Sciences, 2016)
A biological experiment was conducted (2×3×2 factorial design) involving 2 floor spaces (1.25 and 1.90 sq. ft), 3 dietary energy levels (2400, 2600 and 2800 ME kcal/kg) with or without supplementation of commercial multi- enzyme (@ 250g/ton feed) in iso-proteinic diet (protein, 20%) to evaluate growth performance in ‘White turkey’ (CARI Virat) during 8–16 weeks of age. The levels of critical amino acids (lysine and methionine) remained similar in all the diets.Straight-run 120 poults were randomly distributed into twelve experimental groups with four replicate in experimental battery cages (1.64 ft × 2.30 ft) at two different floor spaces (1.25 and 1.90 ft2/bird) from 8th to 16th week of age. The total number of birds per cage were 2 and 3 respectively. Out of 4 replicates, 1 replicate was maintained for the replacement of the dead birds, if any, so as to keep the effective floor space constant throughout the experimental period. Results indicated that body weight, body weight gain, feed intake and feed conversion ratio did not differ significantly due to floor space or enzyme supplementation. Performance index was significantly higher in 1.25 sq. ft. floor space. Overall body weight gain did not differ significantly due to energy levels. Feed intake and feed: gain ratio was significantly lower in group having 2,800 kcal/kg. Performance index was significantly higher in groups fed with 2,600 and 2,800 kcal/kg. Final body weight and cumulative feed intake differed significantly due to interaction between space and energy. Feed enzyme supplementation did not improve performance.Thus the optimum floor space in battery cages for rearing growing turkey poults (8–16 wk) and dietary energy level were 1.25 sq. ft/bird and 2,600 kcal ME per kg diet, respectively.